Prevalence of Anemia in Chronic Kidney Disease (CKD) Patients on Conservative Treatment in Benghazi- 2022 - Jaher , Samia; Elglali , Basma; Sammat , Lameas; Saed , Samira (Scientific Journal of University of Benghazi, 2022)
Background: Anemia is one of the most common and significant complications of chronic kidney disease (CKD) which is related to decreases in the glomerular filtration rate (GFR). Anemia is generally defined as a hemoglobin count of less than 13.0 g/ld in men and less than 12.0 g/dL in premenopausal women. Anemia of CKD is of a multifactorial origin; the widely accepted etiology being decreased renal production of erythropoietin (EPO). Since the kidney's production of erythropoietin serves as the primary stimulus for the production of red blood cells, CKD patients have lower levels of erythropoietin, which in turn can cause anemia. Anaemia in CKD patients is normocytic, normochromic and hypoproliferative. Aim: Determination of proportion and risk factors of anemia in CKD patients. Materials and method: A cross-sectional sectional study with a sample size of 91 CKD patients on conservative treatment. A questionnaire was used to interview patients who had been enrolled in the study. It included sociodemographic data, body mass index (BMI), past medical history, drug history, and laboratory data. Results: The overall prevalence of anemia was 35.2% among CKD patients on conservative treatment. The mean age of patients was 62.9±14.65 SD years and the mean BMI was 27.65±5.5SD. Most of the patients were from the OPD clinic (GFR>15 ml/min/1.73 m2). 60% of the patients were hypertensive and diabetic. Hemoglobin (HB) levels were 10.52 ± 2.7 SD. According to to mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH), the type of anemia observed was normocytic and normochromic. Most of the patients were commonly prescribed an oral and an injectable iron supplement. Conclusion: Anemia was prevalent in CKD patients and the severity increased with the degree of renal damage; however, it is sub-optimally managed. Screening and management of anemia for patients with renal disease should focus more on patients with lower GFR.